EC visa facilitation and readmission agreements: Implementing a new EU security approach in the neighbourhood - Florian Trauner; Imke Kruse (Center for Social and Economic Research (CASE), 2008)
With the Eastern Enlargement successfully completed, the EU is searching for a proper balance between internal security and external stabilisation that is acceptable to all sides. This paper focuses on an EU foreign policy instrument that is a case in point for this struggle: EC visa facilitation and readmission agreements. By looking at the EU's strategy on visa facilitation and readmission, this paper aims to offer a first systematic analysis of the objectives, substance and political implications of these agreements as a means to implement a new EU security approach in the neighbourhood. In offering more relaxed travel conditions in exchange for the signing of an EC readmission agreement and reforming domestic justice and home affairs, the EU has found a new way to press for reforms in neighbouring countries while addressing a major source of discontent in these countries. The analysis concludes with the broader implications of these agreements and argues that even if the facilitated travel opportunities are beneficial for the citizens of the target countries, the positive achievements are undermined by the Schengen enlargement, which makes the new member states tie up their borders to those of their neighbours.
Keywords: 330; EU; EC visa facilitation; readmission agreements; European Neighbourhood Policy; Stabilisation and Association Process; Justice and Home Affairs; Außenpolitik; EU-Nachbarstaaten; Visapolitik; EU-Staaten